A private library in the Age of Enlightenment: The library of The marquis de Montesa - Mendioroz Lacambra, Ana María (Huarte de San Juan. Geografía e Historia, 2009)
The main point of this work is to provide us with some data about the Enlightenedpanorama in the community of Navarra. For that, we have analyzed the funds of the Marquis of Montesa’s library, cofounder of the Real Sociedad Tudelana de los Deseosos del Bien Público, one of the first Sociedades Económicas de Amigos del País. This study not only approaches us to the owner’s ideology, but also helps us to know the spreading of the new school of thought of the Illustration in Navarra.